The Influence of Price, Income, and Lifestyle on Muslim Women's Fashion Purchase Decisions on Shopee - Khoiriyyatul Maghfirotil Manshuroh; Nizar Haris Masruri (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This study aims to analyze the influence of price, income, and lifestyle on fashion product purchasing decisions on the Shopee platform among Muslim female consumers in Ponorogo. Differences in economic conditions and lifestyle are assumed to influence cosumers purchasing decisions when buying fashion product online. Research Methods: This research employed a quantitative approach using questionnaire data collected from 110 respondents. Data analysis techniques used included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and finally, hypothesis testing. Results: The results indicate that price has a significant negative on purchasing decisions (β = -0,264; p = 0,009), while income has a signifcant positive effect (β = 0,765; p = 0,000). Lifestyle does not significantly effect purchasing decicions (β = 0,097; p = 0,383) Simultaneously, these three variables also significantly influence purchasing decisions (F = 16,227; p = 0,000). Conclusion: This indicates that consumer decisions about purchasing fashion products are influenced not only by economic considerations such as price and income level, but also by psychological and social factors such as lifestyle.